Digital Literacy In Problem-Based Learning For Islamic Religious Education - Alifia Oktahariana; Zainuddin Al Haj Zaini; Ach. Faridul Ilmi (IJGIE (International Journal of Graduate of Islamic Education), 2025)
Learning in the current self-paced curriculum emphasizes a student-centered approach, requiring innovation in instructional strategies. At SMA Negeri 1 Jember, East Java, a model integrating Problem-Based Learning (PBL) with digital literacy was implemented in the 2024/2025 academic year for Islamic Religious Education and Ethics. This study critically evaluates the planning, implementation, and assessment of the model, and analyzes its impact on student engagement, critical thinking, and learning outcomes. The research involved 10 Islamic Education teachers and 120 students from grades X and XI, selected through purposive sampling. Employing a qualitative field research approach, data were collected through semi-structured interviews, classroom observations, and documentation analysis. Data analysis followed the Miles, Huberman, and Saldana model, comprising data condensation, data display, and conclusion drawing. Triangulation of sources and methods was applied to ensure validity and reliability. The findings show that the planning phase involved developing digital teaching modules and interactive presentations. Implementation followed a structured sequence of preliminary, core, and closing activities, while assessment utilized observational, formative, summative, and remedial tools. The study affirms that integrating digital literacy into a PBL framework enhances student participation, promotes higher-order thinking, and supports autonomous moral reasoning—key goals in Islamic Religious Education. Rooted in constructivist theory, this model demonstrates practical value for educators aiming to modernize religious instruction while maintaining its ethical and spiritual integrity, particularly within 21st-century digital learning contexts.